Pengaruh Kualitas Pelayanan Dan Corporate Social Responsibility Terhadap Citra Perusahaan Pada Bank Syariah Indonesia Cabang Mataram - Putri, Dinar Febriana; Bambang; Lenap, Indriana Puspitasari (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to empirically test the quality of service and Corporate Social Responsibility on the Corporate Image of Bank Syariah Indonesia, Mataram City. The population in this research is all Sharia Bank customers in Mataram City. The sample technique used is Accedental Sampling. This research is quantitative research that uses primary data from distributing questionnaires as a data source. The number of samples used was 100 customers. The analysis technique used in this research is multiple linear regression analysis with the analysis tool SPSS. The results of the research show that service quality has a significant positive effect on the company's image and Corporate Social Responsibility has a positive and significant effect on the company's image at Bank Syariah Indonesia, Mataram City.